Analisa Dan Perancangan Aplikasi Kependudukan Berbasis Mobile Pada Kecamatan Jelutung - Mafutra, Lian; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2021)
Problems with population administration in Jelutung Subdistrict, Jambi City, the absence of a system to manage population data has resulted in data storage that is still prone to data loss, data redundancy and many third party intermediary practices (broker / extortion) in the service process, this has resulted in the community being reluctant take care of population administration files. The purpose of this study is to analyze and design a population administration system to manage population administration data in Jelutung sub-district in a computerized and mobile-based online administration service for the community. This research uses the UML (Unified Modeling Language) method to design the system. The results of this study resulted in the design of administrative information systems that process population administration files. This design can be developed into an application that can be implemented, and it is expected that this research can be a reference and learning, especially in the field of information systems.